Beach seine fishery of India – A Review - Edwin, Leela; Manju Lekshmi, N.; Yasmi, V. S.; Nath Jha, Paras (Fishery Technology, 2020)
Beach seines are surrounding nets operated with two long ropes, set from the shore for encircling a school of fish in shallow coastal waters. In India, beach seining is the livelihood of the deprived groups of marine fisher. This review article gives an overview of designs, catch composition, prospects, issues and guidelines for the beach seine operations in India. Design of beach seines vary in structure and size based on the geography and resources. Natural and biodegradable materials were used for the fabrication of seine nets which are now replaced with polyamide for its durability and less resistance in water. Motorised and non-motorised wooden/ fibre reinforced plastic sheathed plywood boats are used for the operation of beach seine. Normally beach seines are non-selective fishing gears with small mesh sizes and are operated during the postmonsoon season due to the high availability of coastal pelagics. Studies conducted by ICAR-Central Institute of Fisheries Technology, found that the number of beach seines has been declining in India during the last two decades. ICAR-CIFT has derived technical guidelines for the operation of beach seines along the Indian coast for reduction of juvenile incidence by increasing the existing codend mesh size and recommends square mesh at the cod-end. Suggestions were made to avoid ecologically sensitive areas for beach seine operations. This review article concludes that technical improvements and the introduction of measures for the reduction of juvenile catches will lead to better sustainability and the management of the beach seine fishery which is a source for livelihood for the aged traditional fisherfolk.